Integration of Indigenous Knowledge Systems and Practices (IKSP) in Undergraduate Biochemistry Education: Implications for Student Comprehension and Learning Retention - Edessa G. Flordeliz (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study examined the effectiveness of Indigenous Knowledge Systems and Practices (IKSP) compared to traditional teaching methods in undergraduate biochemistry education. The research focused on student comprehension and knowledge retention over different time frames. Results showed that the IKSP method demonstrated superior immediate effects, with a 60.6% increase from pre-test to post-test, compared to the traditional method's 34.2% increase. However, the traditional method exhibited better short-term retention. Interestingly, after two weeks, the IKSP method outperformed the traditional method in long-term retention, indicating that each method's effectiveness varies depending on the testing timeframe. While the traditional method showed more consistency in immediate application, the IKSP method led to more uniform performance in the long run, particularly in retention. Time and the interaction between time and teaching method were strong predictors of student achievement, explaining 62.5% and 18.6% of the variance, respectively. Based on these findings, the researchers recommend: Integrating both IKSP and traditional methods to leverage their respective strengths at different stages of the learning process; Developing strategies to enhance short-term retention for the IKSP method and long-term retention for the traditional method; and, Implementing continuous evaluation of student progress to optimize adaptive teaching strategies that balance immediate effectiveness, short-term retention, and long-term performance consistency. This study highlights the importance of considering temporal factors in educational method effectiveness and suggests a hybrid approach to maximize learning outcomes in undergraduate biochemistry education.